2021
DOI: 10.3147/jsfp.56.53
|View full text |Cite
|
Sign up to set email alerts
|

Development of Quantitative Real-time PCR and Loop-mediated Isothermal Amplification (LAMP) Assays for Detection of <i>Microsporidium seriolae</i>

Abstract: Beko disease, caused by the Microsporidium seriolae infection, has been a problem in yellowtail aquaculture in western Japan. In recent years, severe cases of this disease have been confirmed, resulting in a significant decrease in product value due to mass mortality and residual cysts. Only polymerase chain reaction (PCR) assays have been reported so far as a detection method for the disease. In this study, quantitative real-time PCR (qPCR) and loop-mediated isothermal amplification (LAMP) methods have been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thirty days from the beginning of the experiment (10 days after the last FBT administration in the 20-d group), all surviving fish were dissected, and visible M. seriolae cysts were counted in the fillet of left side of the body. In addition, qPCR was performed in 10 to 11 randomly selected fish from each group following the protocols described by Mekata et al (2021) and .…”
Section: Clinical Trialmentioning
confidence: 99%
“…Thirty days from the beginning of the experiment (10 days after the last FBT administration in the 20-d group), all surviving fish were dissected, and visible M. seriolae cysts were counted in the fillet of left side of the body. In addition, qPCR was performed in 10 to 11 randomly selected fish from each group following the protocols described by Mekata et al (2021) and .…”
Section: Clinical Trialmentioning
confidence: 99%
“…Although LAMP assays are reliable and sensitive in detecting TiPV‐infected fish, the qPCR assay had 100‐times higher sensitivity than the LAMP assay. Similarly, the sensitivity of the LAMP assay has been reported to be lower than the qPCR method for the detection of other fish pathogens, including TiLV (Phusantisampan et al, 2020), iridovirus (Yu et al, 2022), and Microsporidium seriolae (Mekata et al, 2021). Various factors, including differences in polymerase enzymes, the target positions of the primers, and the size of the amplicons, could affect amplification efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the sensitivity of the LAMP assay has been reported to be lower than the qPCR method for the detection of other fish pathogens, including TiLV (Phusantisampan et al, 2020), iridovirus (Yu et al, 2022), and Microsporidium seriolae (Mekata et al, 2021).…”
Section: Sensitivity Of the Tipv Lamp Assaymentioning
confidence: 99%
“…However, it has often been shown that M. seriolae and Kabatana species does not make a monophyletic clade (McGourty et al ., 2007 ; Casal et al ., 2010 ; Liu et al ., 2019 ). The available SSU rDNA sequences of M. seriolae in the INSDC database lack the first 300–400 nucleotides in the 5′ end (Bell et al ., 2001 ; Mekata et al ., 2021 ) and this may decrease phylogenetic resolution by shortening the resultant alignment dataset. In this study, we succeeded to determine the lacking region and obtained almost full length of the SSU rDNA (1328 bp) for M. seriolae .…”
Section: Discussionmentioning
confidence: 99%